Philosophical reflection drawn from the experience of the design weaknesses of PhD students through research activities - Bruce, Bemena; Aurélien, JERSON; André, TOTOHASINA; Daniel Rajaonasy, FENO; -, ARMAND (Journal of Research and Multidisciplinary, 2025)
The productivity generated by doctoral research activities requires exclusively laborious work in order to have yields with all the qualities practically satisfactory for these tasks. The implementation of the state of the art and the construction of a "preprint" are among the occupations of capital importance among the conditions necessary to complete a thesis. They need more very specific knowledge, in other words, full of joy, will, passion, intuition, etc. Faced with this circumstance, doctoral students sometimes have often invalid excuses brought by complexes of uncertainties. Subsequently, this paper explains “how can a PhD student appropriate the working methods in order to enable him to manage his thesis work as well as possible? ".